2020
DOI: 10.1016/j.breast.2020.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with multidisciplinary team recommendations and disease outcomes in early breast cancer patients: An analysis of 4501 consecutive patients

Abstract: Background Multidisciplinary team (MDT) discussions are widely held to facilitate the diagnosis and treatment of breast cancer, but patient compliance with the MDT recommendations and the impact of compliance on disease outcome are uncertain. Methods We conducted a retrospective review of data from a prospective database of breast cancer patients treated at Shanghai Ruijin Hospital between April 2013 and August 2018. MDT discussions were held for all patients before the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 23 publications
(35 reference statements)
1
26
0
Order By: Relevance
“…Forty-one articles investigated the effect of MDTMs on cancer care pathways in colorectal cancer (21/41) , lung cancer (10/41) [38][39][40][41][42][43][44][45][46][47], prostate cancer (6/41) [48][49][50][51][52][53] and breast cancer (4/41) [54][55][56][57] (Table 1). All studies were conducted in adults (total n = 82,073, range 42-32,569 study subjects per study, mean 2002), with studies originating from in Oceania (8/41) [20,26,29,38,39,43,45,52], Asia (9/41) [18,21,23,35,41,46,50,56,57], Europe (13/41) [17,19,24,25,27,31,32,34,36,37,44,…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Forty-one articles investigated the effect of MDTMs on cancer care pathways in colorectal cancer (21/41) , lung cancer (10/41) [38][39][40][41][42][43][44][45][46][47], prostate cancer (6/41) [48][49][50][51][52][53] and breast cancer (4/41) [54][55][56][57] (Table 1). All studies were conducted in adults (total n = 82,073, range 42-32,569 study subjects per study, mean 2002), with studies originating from in Oceania (8/41) [20,26,29,38,39,43,45,52], Asia (9/41) [18,21,23,35,41,46,50,56,57], Europe (13/41) [17,19,24,25,27,31,32,34,36,37,44,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…All studies were conducted in adults (total n = 82,073, range 42-32,569 study subjects per study, mean 2002), with studies originating from in Oceania (8/41) [20,26,29,38,39,43,45,52], Asia (9/41) [18,21,23,35,41,46,50,56,57], Europe (13/41) [17,19,24,25,27,31,32,34,36,37,44,48,49], North America (10/41) [22,28,30,33,40,42,47,51,53,54] or Africa (1/41) [55]. Studies were performed in multicenter (6/41) [34,37,38,40,41,56] or single-center (35/41) [17][18]…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…It could be conducive to evidence-based decisions for clinicians and provide a convenient medical treatment process for patients [15,16]. Our previous studies demonstrated that MDT discussion could also lower the relative risk of relapse by 16% and the risk of death by 11% in patients with breast cancer [7]. However, a major difficulty after the MDT meeting and during the treatment process was maintaining patient compliance.…”
Section: Mdt In Breast Cancermentioning
confidence: 99%